External Indebtedness of Developing Countries - Baumgartner, Ulrich (Occasional Papers; Occasional Paper ;, 1981)
The external indebtedness of non-oil developing countries has been of growing concern in recent years. Several factors have brought the debt issue to the forefront of the problems facing a number of countries, including the rapid rise in extenal debt in the recent past, changes in the composition of debt (toward a greater proportion owed to commercial banks) and the attendant deterioration in the terms of debt, and the rise in debt service resulting from these developments.